A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America - Duan, Yani; Dietrich, Christopher H. (Zootaxa, 2018)
Polyamia (Polyamia) choromorica sp. n., representing the first record of the genus Polyamia DeLong from South America, is described and illustrated. Previously described species of Polyamia DeLong appear to be restricted to North America. Color illustrations of Polyamia (Copolyamia) caperata (Ball), Polyamia (Copolyamia) similaris DeLong & Davidson and Polyamia (Polyamia) weedi Van Duzee are also provided for comparison. A species checklist and distribution summary for the genus is provided. Notes on other South American species of Deltocephalini with supernumerary forewing crossveins are also provided.